Adsorption Efficiency, Adsorption Isotherms and Kinetic Study for Methylene Blue Removal in Aqueous Solution of Thiol-Functionalized Mesoporous Silica Nanospheres - Chueachot, Romteera; Khankam, Kewalee; Lakathok, Atcharaphan; Jarussophon, Suwatchai; Nakhowong, Ronariddh (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Thiol-functionalized mesoporous silica nanospheres material was synthesized by co-condensation method under biphasic system. Structural characterization comfirmed the mesoporous structure and the content of adsorbents by transmission electron microscopy, N2 adsorption-desorption and Fourier transform inferred spectroscopy. The adsorbent were nanosphere with particle diameter lower than 50 nm. A batch adsorption study was carried out with variable pH, adsorption time, adsorbent dose, shaking rate, temperature and adsorbate concentration. Methylene blue could be removed by 0.05 g of MSN and MSN-SH at pH 10 and 30 min of adsorption time. The adsorption process followed pseudo-second-order kinetics. The experimental adsorption isotherm was found to be best fitted with the Langmuir model, which implied that the adsorption of MB as a monolayer.